Onion-shell nuclei on monolayer MoS2 facilitate friction reduction - Haowen Luo; Shenghong Liu; Zhihuan Li; Yuan Li; Alain Dubois; Yadong Xu; Nan Kang; Mohamed El Mansori; Feng Zhou; Jianxi Liu (Friction)
Monolayer MoS2 has garnered significant interest because of its exceptional optoelectronic and tribological properties and potential application as a lubrication layer in micro- and nanoelectromechanical systems. Although the nanotribological performance of chemical vapor deposition (CVD)-grown MoS2 and the characteristics associated with CVD growth have been extensively studied, challenges remain in designing specific regions on the monolayer MoS2 surface with reduced friction. Here, we develop nuclei with an onion-shell structure on CVD-grown monolayer MoS2 to achieve remarkable friction and adhesion reduction. These nuclei, dispersed on high-quality and crystalline MoS2, consist of an oxi-sulfide core surrounded by a multilayer MoS2 shell. Lateral force microscopy results indicate that onion-shell nuclei create an ensemble effect that decreases friction and adhesion by up to 45% and 20%, respectively, compared with those of MoS2 because of the multilayer structure and in-plane tensile strain, both of which minimize out-of-plane deformation. Derjaguin–Müller–Toporov (DMT) model calculations and step-down load‒friction correlations illustrate that the work of adhesion, shear strength, and coefficient of friction on the nucleus decrease by more than 22%, 19%, and 34%, respectively, compared with those on MoS2. The onion-shell nucleus presents a novel lubrication strategy to mitigate friction and adhesion in CVD-grown two-dimensional (2D) materials, with potential applications in lubricating nanoscale friction pairs.